APLIKASI ROOTED TREES PADA METODE RUNGE-KUTTA - , TRI KUNCORO PRASETYO HUTOMO, Dr. Sumardi, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Runge-Kutta is a method to estimate the exact value of a differential equation with initial value. This method basically has a general equation containing constants with unknown value. We can find the value of these constants by expand a general equation of Runge-Kutta method with Taylor expansion and is equated by Taylor expansion of the exact solution of a differential equation. However, the Taylor expansions would be cumbersome performed when it reaches a high level derivative. Therefore, both Taylor expansion of Runge-Kutta methodâs general equation and Taylor expansion of exact solution of a differential equation need to be connected with the labeling on rooted trees. So, we can find the value of the constants of Runge-Kutta method simply by applying the labeling.